The Effects of Lighted Incubation on Traits and Composition of Broiler Breast Meat - Esin Ebru Onbaşılar; Hilal Çapar Akyüz; Umut Can Gündoğar; Sakine Yalçın; Tevhide Sel; Emirhan Nemutlu; Tuba Reçber; Banu Yüceer Özkul; Necmettin Ünal; Ceyhan Özbeyaz (Veterinary Medicine and Science)
ABSTRACT Background During incubation, the formation of fundamental anatomical and physiological structures of broilers makes this period highly sensitive to environmental factors. Objectives This study examined the effects of green LED lighting (560 nm, 15 lux) during incubation on the quality characteristics of broiler breast meat. Methods Meat samples were analysed for pH, colour (L*, a*, b*), cooking loss, water holding capacity, proximate composition (dry matter, crude protein, fat, and ash), fatty acid composition, amino acid profile, and antioxidant properties. Results Green LED lighting had no significant impact on ultimate pH, meat colour, cooking loss or water holding capacity (P>0.05) but resulted in a higher initial pH (p < 0.05). Nutrient composition was found similar between groups (p > 0.05). It increased certain saturated fatty acids (C17:0, C20:0, C23:0), DHA (C22:6n3), asparagine and glutamine (p < 0.05), which may enhance nutritional value. Although TAS levels were elevated, higher TOS and OSI values indicate increased oxidative stress (p < 0.05). Conclusion These findings suggest that green LED lighting during incubation can positively influence certain meat quality traits, particularly fatty acid and amino acid composition. Future studies should focus on optimising lighting protocols during the incubation to enhance meat quality while minimising oxidative stress.